2019
DOI: 10.1039/c9cp04658e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pressure-induced nanocrystal superlattice formation

Abstract: The formation of superlattices from aqueous suspensions of PEGylated gold nanocrystals at high hydrostatic pressure is studied by means of time-resolved small angle X-ray scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This was further investigated in time‐resolved experiments after a pressure jump. [ 89 ] Therein, the pressure was raised from below to above the crystallization pressure within few milliseconds. The subsequent supercrystal formation and growth was tracked by time‐resolved SAXS.…”
Section: X‐ray Scattering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was further investigated in time‐resolved experiments after a pressure jump. [ 89 ] Therein, the pressure was raised from below to above the crystallization pressure within few milliseconds. The subsequent supercrystal formation and growth was tracked by time‐resolved SAXS.…”
Section: X‐ray Scattering Methodsmentioning
confidence: 99%
“…[ 2,85,86 ] It should be noted, however, that also very fast (in the range of seconds) self‐assembly protocols based on solvent evaporation are reported [ 60 ] and supercrystal formation in seconds by high‐temperature crystallization [ 87 ] or induced by hydrostatic pressure has been observed. [ 88,89 ] As discussed above, attractive interparticle interactions are not crucial for self‐assembly. Well‐ordered entropy‐driven assembly is well known for hard‐spheres and rods.…”
Section: Self‐assembly Of Nanoparticlesmentioning
confidence: 99%
“…They concluded that the decreasing of the lattice constant is primarily due to the compression of the PEG layer, because the Au core shape was not modified [82]. In the same research group, Lehmkühler et al studied the kinetics of the supercrystal formation induced by pressure [83]. The authors have taken the same radius of 6 nm than previously for the gold spherical nanoparticles (AuNPs) functionalized with α-methoxypoly(ethylene glycol)-ω-(11-mercaptoundecanoate) ligands (PEGMUA).…”
Section: Use Of High Pressures For the Supercrystal Formation Of Gold Nanoparticlesmentioning
confidence: 99%
“…The time scale of this supercrystal formation has varied from 25 s to 0.3 s with the increasing of the pressure jump. This effect is linked to an improvement of the crystal quality caused by a larger speed of supercrystal formation [83].…”
Section: Use Of High Pressures For the Supercrystal Formation Of Gold Nanoparticlesmentioning
confidence: 99%
“…We recently observed well-defined crystallization directly from aqueous particle suspensions induced by pressure for PEGylated spherical AuNP. 20,21 This crystallization is fast and largely reversible. Unlike previous high pressure studies on NP assemblies starting with preordered crystals, [22][23][24][25][26][27] in our approach we observe pressure-induced crystallization directly from the liquid state.…”
Section: Introductionmentioning
confidence: 99%